Enhancing manufacturing efficiency with notch-enabled tooling: Cost-effective osmotically controlled release tablets using metformin HCl - Kirpa Shanker Tiwari, Parijat Pandey, Harish Dureja, Munish Garg (Journal of Applied Pharmaceutical Science, 2025)
Laser drilling is commonly used in the production of osmotic-controlled release tablets but is expensive and time-consuming. An alternative is using customized tooling to compress the tablet blend and create the required orifice, which can reduce costs and improve efficiency. This study presents a cost-effective approach using a specially designed notch-enabled tool to replace laser drilling in osmotic tablet manufacturing. A 21 × 10 mm oval-shaped tool with a 0.7 mm notch and tapered dies was designed using S7 material to assess feasibility. Metformin hydrochloride (HCl) osmotic tablets were formulated using controlled notch tooling, eliminating the laser drilling step. Core composition, coating materials, and coating parameters were optimized via full factorial design. The formulation was refined by adjusting the ratios of povidone K29/30 and sodium lauryl sulfate, while the coating used 15% polyethylene glycol with a 90:10 acetone-to-water ratio. The coating process was optimized with specific spray rates and bed temperatures. Tablet evaluation included parameters such as bulk density, disintegration time, hardness, friability, and in vitro dissolution. This approach led to the efficient manufacturing of Metformin HCl extended-release tablets, improving swallowability and minimizing weight gain, without the need for laser drilling. This notch-enabled tooling method shows significant potential for industrial-scale production.
Keywords: Osmotic drug delivery, cost reduction, tooling, laser drilling, DoE